Evaluating the effects of forward guidance and large-scale asset purchases - Xu Zhang (Bank of Canada, 2021)
This paper evaluates the effects of forward guidance and large-scale asset purchases (LSAP) when the nominal interest rate reaches the zero lower bound. I investigate the effects of the two policies in a dynamic new Keynesian model with financial frictions adapted from Gertler and Karadi (2011, 2013), with changes implemented so that the framework delivers realistic predictions for the effects of each policy on the entire yield curve. I then match the change that the model predicts would arise from a linear combination of the two shocks with the observed change in the yield curve in a 30-minute window around Federal Reserve announcements, allowing me to identify the separate contributions of each shock to the effects of the announcement. My estimates imply that LSAP was more important in influencing output and inflation than forward guidance.
Keywords: E; E5; G; G0; 330; Business fluctuations and cycles; Central bank research; Econometric and statisticalmethods; Interest rates